2016
DOI: 10.1108/jstp-10-2014-0242
|View full text |Cite
|
Sign up to set email alerts
|

Value proposition test-driving for service innovation: how frontline employees innovate value propositions

Abstract: Purpose This article investigates the role of frontline employees in service innovation from a service-dominant logic perspective. Frontline employees lack a formal innovation obligation. Service innovation is a resource integration process resulting in the creation of new value propositions. Design/methodology/approach A case study of service innovation projects that includes three different businesses in the IT sector and personal interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…As the interface between customers and the organization, frontline employees are a key source of competitive advantage for service organizations. Not only are frontline employees the “face” of the organization, they are also responsible for innovations in service delivery and value co-creation (Åkesson et al , 2016). Intercultural service interactions carry far reaching implications for firms, employees, as well as customers, by offering both a unique challenge and an opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…As the interface between customers and the organization, frontline employees are a key source of competitive advantage for service organizations. Not only are frontline employees the “face” of the organization, they are also responsible for innovations in service delivery and value co-creation (Åkesson et al , 2016). Intercultural service interactions carry far reaching implications for firms, employees, as well as customers, by offering both a unique challenge and an opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…This group of studies highlights the different fields that have contributed to the analysis of customer value co-creation in service innovation (Jaakkola et al, 2015;Chew, 2016;Joly et al, 2019). Starting from this multidisciplinarity, but always focused on service innovation, the documents included in the cluster have analyzed different issues: service experience co-creation (Jaakkola et al, 2015), the relationship between value co-creation and service evaluation (Foglieni and Holmlid, 2017), and the role of different stakeholders (Karlsson and Skalen, 2015;Akesson et al, 2016;Jonas et al, 2016;Jonas and Roth, 2017). Yu and Sangiorgi (2018) state that "Service design, as a human-centered and creative approach to service innovation, can reframe new service development processes to implement value co-creation."…”
Section: Value Co-creation In Service Innovation Ecosystems (Marine Bmentioning
confidence: 99%
“…All of these roles have been analyzed in recent years, because of their potential to affect firms' competitive advantage. Also, the phenomenon of value co-creation has extended to other stakeholders, to study their contribution to the innovation process (Akesson et al, 2016). Value co-creation related to technology and innovation management has expanded in several industries, with special intensity in services (tourism, health, and public services) but not exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…Schepers et al (2012) found that a sense of moral responsibility for customer welfare has a stronger impact on service behavior under a low level of organizational control. Furthermore, co-creation of service is a critical characteristic of services (Åkesson et al , 2016; Galvagno and Dalli, 2014; Mustak et al , 2013; Vargo and Lusch, 2008; Verleye et al , 2016). Because the onus of value-creation moves from the producer to collaborative co-creation between parties, the producer-customer distinction becomes irrelevant.…”
Section: Moral Dilemmas In Service Rolesmentioning
confidence: 99%